Kampus Tanpa Plastik: Strategi Edukatif dan Praktis dalam Membangun Budaya Ramah Lingkungan - Lasaiba, Mohammad Amin; Riry, Roberth Berthy (Universitas Pattimura, 2025)
The “Plastic-Free Campus” program at FKIP Pattimura University was implemented to address the increasing use of single-use plastics and low ecological awareness among students. The program aimed to build an environmentally friendly campus culture through education, campaigns, and practical strategies for reducing plastic waste. The method applied was Participatory Action Research (PAR), involving participatory observation, socialization, Focus Group Discussions (FGD), training, and direct mentoring. Results showed a 32-point increase in students’ understanding between pre-test and post-test, a 23% reduction in plastic waste in the canteen, and the emergence of new habits such as bringing personal utensils and sorting waste. The program demonstrated that educational and participatory approaches effectively foster sustainable ecological behavior among students. It implies the need for institutional policy support and program replication to expand environmental initiatives in higher education.